Effect of plasma spraying power on LSGM electrolyte of metal-supported solid oxide fuel cells. (August 2017) - Hwang, Chang-Sing; Hwang, Te-Jung; Tsai, Chun-Huang; Chang, Chun-Liang; Yang, Sheng-Fu; Wu, Ming-Hsiu; Fu, Cheng-Yun
Abstract: Four nickel-iron metal-supported solid oxide fuel cells with a diameter of 2.4 cm and a cathode active area of 1.76 cm 2 are fabricated by atmospheric plasma spraying (APS) and heat-treated in air at 850 °C and 500 g cm −2 pressure for 4 h. These cells with the same functional layer materials have electrolyte layers produced by different APS torch powers, but the APS fabrication parameters for other functional layers of these cells are kept the same. XRD data show that there is a LaSrGaO4 impurity phase in the prepared dense LSGM electrolyte produced at 54 kW torch power. According to experimental data on the current-voltage-power and AC impedance measurements at temperatures ranging from 550 to 800 °C, the cell with dense LSGM electrolyte produced at 52 kW torch power has the best power performance and the lowest electrolyte resistance and the corresponding delivered power densities at 0.7 V for 550, 600, 650, 700, 750 and 800 °C temperatures are 0.147, 0.271, 0.426, 0.585, 0.716 and 0.796 W cm −2, respectively.